The influence of temporary occlusion of parent vessel on outcome of surgical treatment of ruptured cerebral aneurysms - Nikolov, Vesna; Radisavljević, Miša; Jelenković, Boban; Anđelković Apostolović, Marija (Vojnosanitetski pregled, 2020)
Background/Aim. Aneurysm rupture followed by subarachnoid or intracerebral haemorrhage is always current topic and poses a great challenge to neurosurgeons. The aim of the study was to establish whether applying temporary occlusion before placing a final clip was justified. Methods. A prospective study was conducted on patients with aneurysm rupture, treated at Neurosurgical Clinic in Niš from January 2012 to December 2016. Patients belonging to I and II and 1, 2 and 3 grades according to the Hunt-Hess grading system and Fisher scale, respectively, were monitored. Results. In 85, out of total 182 bleeding aneurysms that were treated, a neurosurgeon decided to apply temporary clipping before placing the final clip. Temporary occlusion significantly influenced the presence of resulting neurological deficit. Conclusion. The application of temporary occlusion facilitates placing the final clip but also affects the occurrence of neurological deficits. It is assumed that this is a consequence of caused vasospasm, considering that these are bleeding aneurysms.